Melestarikan Nilai Kaharingan dalam Iman Katolik : Pendekatan Katekese Inkulturasi di Stasi Santa Anastasia Muara Napu - Martina Minaratih; Teresia Noiman Derung (Lembaga Pengembangan Kinerja Dosen, 2024)
This article discusses the role of inculturation catechesis in Catholic faith formation for people with a Kaharingan faith background in Stasi Santa Anastasia Muara Napu, Mandam Parish, Diocese of Banjarmasin. Since 2014, there has been a gradual transition from Kaharingan to Catholicism in this area, which presents important challenges in integrating Catholic teachings with the strong Kaharingan culture. This descriptive qualitative research explores the strategic role of catechists as facilitators in delivering Catholic teachings in harmony with local traditions. The approach includes coaching for parents as the main pillar in the family and the Church, as well as how the inculturation process can help maintain the balance between faith and cultural identity. The results show that the inculturation approach by integrating the teachings of the Catholic faith and local culture is able to increase acceptance of Catholic teachings without compromising the cultural heritage of the people. The findings highlight the important role of catechists in accompanying the conversion process and supporting people in building families rooted in their traditional values.